Management and outcome of 239 adolescent and adult rhabdomyosarcoma patients. (15th July 2013) - Dumont, Sarah N.; Araujo, Dejka M.; Munsell, Mark F.; Salganick, Jason A.; Dumont, Amaury G.; Raymond, Kevin A.; Linassier, Claude; Patel, Shreyaskumar; Benjamin, Robert S.; Trent, Jonathan C.
Abstract: Adult rhabdomyosarcoma (RMS) is a rare tumor that has inferior outcome compared to younger patient population. The present work aims to study the age‐related differences in management of adolescents and adults with RMS. Under an institutional review board‐approved protocol, we retrospectively analyzed 239 patients, 10 years of age and greater, diagnosed with RMS at MD Anderson Cancer Center from 1957 through 2003. Of the 239 patients, 163 patients were nonmetastatic with a median overall survival (OS) of 3.8 years (95% CI 2.8–7.6). In the multivariate analysis, age >50 was significantly associated with shorter OS and recurrence‐free survival (RFS) for primary patients. Metastases were present in 76 patients, the median OS was 1.4 years. Approximately 13% of metastatic patients <50 years old had a long‐term survival exceeding 15 years. Multimodality therapy, including surgery, radiotherapy, and chemotherapy was significantly associated with longer OS in primary and metastatic patients. Use of bi‐ and triple modality treatment decreased in metastatic patients over 50 years of age compared to younger patients. RMS in adolescents and adults has a poor outcome compared with younger individuals. Increased use of multidisciplinary therapy may improve older patient clinical outcome. Abstract : Adult rhabdomyosarcoma is a rare entity that has inferior outcome compared to younger patient population. This retrospective study emphasizes the age‐related differences in management of patients that may partly explain their poor prognosis.